PEDAGOGICAL WORK FOR STUDENTS WHO ARE THE TARGET-AUDIENCE OF SPECIAL EDUCATION: INVESTIGATING INCLUSION IN CHILDREN'S EDUCATION - Fachinetti, Tamiris Aparecida [UNESP]; Barboza do Nascimento, Beatriz A. [UNESP]; Mosca Giroto, Claudia Regina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The performance of the teacher of childhood education with the students of special education target public has assumed relevance in the inclusive educational context, since the mediation of this teacher, as well as the adoption of methodologies consistent with this perspective, this educational stage is crucial for ensuring access, retention and participation of those students in school from the beginning of their schooling process. Subsidized by such ideas, this study aimed to investigate, in the regular classroom, how is the teacher's practices in the children's education, to the students of special education target public with a view to the appropriation of the curriculum by that public. Observations were carried out in four classrooms of teachers that were acting in childhood education classes, which were counting with students of special education target public registered in in four schools in two cities in the countryside of Sao Paulo. The results of this study demonstrated how these students were included in the developed activities, as well how the teachers used their teaching practice to attend to all students, and particularly those who found themselves characterized as special education target public.
Keywords: Childhood education; Inclusive education; Teacher's training; Teaching practices; Special education target public